Clostridium perfringens : - Jong, Aarieke Eva Irene de (Wageningen Universiteit, 2003)
To predict worst-case scenarios of the behavior of this pathogen in food, research should not focus on a couple of strains. To limit excessive screening of strains, a gamma-type growth model, based on general and interpretable parameters, was shown to accurately predict growth of c. perfringens.